Pengaruh Harga Minyak dan Suku Bunga Terhadap Harga Saham Sub Sektor Makanan Minuman di BEI - Dwi Ermayanti Susilo; Moh. Usman Rusli (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to analyze the effect of oil prices and interest rates on stock prices of manufacturing companies in the food and beverage sub-sector listed on the IDX. The study uses quantitative research methods which are carried out through data collection with secondary data, the population is the Financial Statements of food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2021 period. The sample in this study is in the form of balance sheets and profit/loss reports for manufacturing companies in the food and beverage sector listed on the Indonesia Stock Exchange (IDX) for the 2016-2021 period, data analysis using multiple Linear Regression statistical methods and hypothesis testing. The results show that 1) The oil price variable has no effect on the stock price of manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) for the period 2017-2021 2) The interest rate variable has an effect on stock prices in manufacturing companies in the food and beverage sub-sector. beverages listed on the Indonesia Stock Exchange (IDX) for the period 2017-2021